REVERSIBLE DISAGGREGATION OF MYOFILAMENTS IN VERTEBRATE SMOOTH MUSCLE - Fay, Fredric S. (The Rockefeller University Press, 1973)
Strips of taenia coli from guinea pigs were incubated under isometric conditions in Krebs-Ringer bicarbonate saline (MKR) containing various concentrations of Ca(+2) and/or Mg(+2). Spontaneous or chemically induced contractile activity was abolished within 15 min of exposure to MKR containing Ca(+2) at concentrations below 10(-6) M; contractile activity was restored by reincubation in normal MKR after 1–2 h. Exposure of taenia coli to MKR containing Ca(+2) at concentrations below 10(-6) M for 1 h or more led to loss of thick and thin myofilaments from the sarcoplasm as observed with the electron microscope. Except for the loss of these two filament types, the cells contained all other structural features observed in preparations incubated in MKR containing Ca(+2) at its normal level (1.3 x 10(-3) M). The loss of thick and thin myofilaments in strips exposed to a Ca(+2) concentration below 10(-6) M was reversed by reincubation for 30 min in MKR containing normal Ca(+2) levels. The observed loss of thick and thin myofilaments in response to low Ca(+2) is interpreted as resulting from the disaggregation of some or all of the molecular components of these two filament types.